2020
DOI: 10.1108/ijchm-03-2020-0211
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hotel employees’ regulatory foci and voice behavior: the moderating role of leader-member exchange

Abstract: Purpose Drawing on leader-member exchange theory and regulatory focus theory, the purpose of this study is to explore the effects of hotel employees’ regulatory foci on their voice behavior and the moderating role of leader-member exchange. Design/methodology/approach The questionnaire includes demographics, regulatory foci, leader-member exchange and voice behavior sections. The data was collected via a survey of 10 international tourist hotels in Taiwan and 479 valid questionnaires were completed. Confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 89 publications
(118 reference statements)
2
15
0
Order By: Relevance
“…The result showed that employee openness and resistance to change partially mediate the relationship between technological turbulence and resilience. The findings support the previous argument that openness to change encourages employee productivity and performance, whereas resistance to change decelerates employees’ intention to respond to turbulent environments (Ariza-Montes et al , 2017; Chiu et al , 2020; Dai et al , 2020; Hon et al , 2014). The available literature highlighted the importance of employee resilience to cope with TT.…”
Section: Conclusion and Theoretical Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…The result showed that employee openness and resistance to change partially mediate the relationship between technological turbulence and resilience. The findings support the previous argument that openness to change encourages employee productivity and performance, whereas resistance to change decelerates employees’ intention to respond to turbulent environments (Ariza-Montes et al , 2017; Chiu et al , 2020; Dai et al , 2020; Hon et al , 2014). The available literature highlighted the importance of employee resilience to cope with TT.…”
Section: Conclusion and Theoretical Implicationssupporting
confidence: 88%
“…Less is clearly known about the boundary conditions of crisis relationship leadership efficacy in hospitality literature, whether or why some employees are responsive and willing to the turbulent business environment, whereas others are not (Dai et al , 2020; Giousmpasoglou et al , 2021; Tuan, 2018).…”
Section: Moderating Effect Of Crisis Leadership Efficacymentioning
confidence: 99%
“…While the negative impact of customer mistreatment on employee outcomes must be acknowledged, our findings suggest that, to some extent, customer mistreatment could positively affect customer-focused voice. Because customer-focused voice can help organizations discover and recognize service failure issues (Dai et al , 2021; Lam and Mayer, 2014), hotels should educate frontline employees with real examples of how customer mistreatment could benefit the organization and help the management team identify customer-service issues. Then, because customer mistreatment can impair frontline employees’ OBSE , hotels may consider communicating such messages as “do not take it personally” to frontline employees.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the constant changes in the hospitality industry, hotels must rely on frontline employees who directly interact with the customers to gain first-hand knowledge about consumer needs and demands (Dai et al , 2021; Peng et al , 2021). Their role in identifying potential problems or issues in service delivery, and making constructive suggestions, is particularly pivotal for the effectiveness and efficiency of hospitality organizations (Han and Hwang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that voice behavior benefits workplaces and organizations [18][19][20]. Studies have also indicated that voice behavior has numerous antecedents, including commitment to change [21], encouragement to participate [22], moral leadership, authoritarian leadership [23], person-organization fit [1], psychological capital [24], team-member exchange [25], transformational leadership [26], regulatory foci [18], supervisor empowerment [27], and work engagement [28]. Paternalistic leadership may also be an antecedent of hotel employees' voice behavior.…”
Section: Voice Behaviormentioning
confidence: 99%